ANALYSIS OF THE EFFECTIVENESS OF TAX COLLECTION AND ENTERTAINMENT TAX RETRIBUTION ON LOCALLY-GENERATED REVENUE IN BATAM CITY - Ronald Wangdra (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
The purpose of this study is to find answers about the level of Entertainment Tax Retribution collection in Batam City and its contribution to local tax revenue. This research uses a descriptive analysis method, focusing on Batam City. The sampling technique used is non-probability sampling, that is, the technique of determining the sample using certain considerations or using financial statements for the years 2017-2021. The results of hypothesis testing using multiple regression analysis methods show that the Entertainment Tax Retribution collection and payment performance of Batam City Dispenda has a significant impact on Locally-generated revenue. Although partial Effectiveness of Tax Collection in Batam City Dispenda has a significant relationship with the initial income of the region, however